Better nutrition, health, and wealth: The role of informal markets in future food systems - International Livestock Research Institute (International Livestock Research Institute, 2021)
Policymakers can't afford to ignore informal markets anymore. Join us for a Nutrition for Growth Summit 2021 side event on 2 December. Register free: https://ilri-org.zoom.us/webinar/register/WN_wuCEwIt2RHOh8GZyncx7iQ